Foreign Direct Investment and Poverty Reduction - Klein, Michael; Aaron, Carl; Hadjimichael, Bita (World Bank, Washington, DC, 2014)
Foreign direct investment is a key ingredient of successful economic growth and development in developing countries--partly because the very essence of economic development is the rapid and efficient transfer and cross-border adoption of "best practices." Foreign direct investment is especially well suited to effecting this transfer and translating it into broad-based growth, not least by upgrading human capital. Growth is the single most important factor in poverty reduction, so foreign direct investment is also central to achieving that important World Bank goal. Government-led programs that improve social safety nets and explicitly redistribute assets and income might direct more of the fruits of growth to the poor. But these are complements--not alternatives--to sensible growth-oriented policies. And growth is needed to fund these government-led programs. Moreover, the delivery of social services to the poor--from insurance schemes to such basic services as water and energy--can clearly benefit from reliance on foreign investors. In short, foreign direct investment remains one of the most effective tools in the fight against poverty.